Adipocyte-secreted exosomal microRNA-34a inhibits M2 macrophage polarization to promote obesity-induced adipose inflammation - Pan, Yong; Hui, Xiaoyan; Hoo, Ruby Lai Chong; Ye, Dewei; Chan, Cyrus Yuk Cheung; Feng, Tianshi; Wang, Yu; Lam, Karen Siu Ling; Xu, Aimin (The Journal of clinical investigation, 2019)
Persistent, unresolved inflammation in adipose tissue is a major contributor to obesity-associated metabolic complications. However, the molecular links between lipid-overloaded adipocytes and inflammatory immune cells in obese adipose tissues remain elusive. Here we identified adipocyte-secreted microRNA-34a (miR-34a) as a key mediator through its paracrine actions on adipose-resident macrophages. The expression of miR-34a in adipose tissues was progressively increased with the development of dietary obesity. Adipose-selective or adipocyte-specific miR-34a-KO mice were resistant to obesity-induced glucose intolerance, insulin resistance, and systemic inflammation, and this was accompanied by a significant shift in polarization of adipose-resident macrophages from proinflammatory M1 to antiinflammatory M2 phenotype. Mechanistically, mature adipocyte-secreted exosomes transported miR-34a into macrophages, thereby suppressing M2 polarization by repressing the expression of Krüppel-like factor 4 (Klf4). The suppressive effects of miR-34a on M2 polarization and its stimulation of inflammatory responses were reversed by ectopic expression of Klf4 in both bone marrow-derived macrophages and adipose depots of obese mice. Furthermore, increased miR-34a expression in visceral fat of overweight/obese subjects correlated negatively with reduced Klf4 expression, but positively with the parameters of insulin resistance and metabolic inflammation. In summary, miR-34a was a key component of adipocyte-secreted exosomal vesicles that transmitted the signal of nutrient overload to the adipose-resident macrophages for exacerbation of obesity-induced systemic inflammation and metabolic dysregulation.